Analysis Of the Reasons for Merchants’ Reluctance to Accept Electronic Payment Methods - Mansour Omar Altwergi, Fouad (International Journal of Social Science, Education, Communication and Economics, 2024)
This study aims to determine the reasons behind customers' reluctance to adopt electronic payments and how these factors relate to their values. To identify the characteristics of electronic payments that customers find objectionable and to look into the relationships between those characteristics and people's values by looking at the effects of those characteristics; to offer advice to financial institutions and service providers on how to develop appropriate strategic plans to promote electronic payments in Libya. To achieve these research objectives, the means-end chain (MEC) theory is applied in combination with hard laddering interviews as a data collection method. Subsequently, the data is analyzed using the Association Pattern Technique (APT) to produce the Hierarchical Value Map (HVM). The HVM identifies five main obstacles that keep customers from using electronic payments: a lack of awareness about the benefits and security of electronic payments, a lack of laws protecting users of electronic payments, the unpopularity of electronic payments, the cost of transactions, and the lack of e-payment discounts. The Value Map also revealed that the most important value, safety, can explain the bulk of customers' reluctance to accept electronic payments. The respondents also expressed significant concerns about the economy and the convenience of e-payments. The report offers suggestions for banks and service providers to increase e-payment usage based on these findings.